2020
DOI: 10.1039/c9pp00032a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV radiation and altitude characteristics on the functional traits and leaf optical properties in Saxifraga hostii at the alpine and montane sites in the Slovenian Alps

Abstract: UV radiation affects the biochemical, physiological and morphological responses of plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…In addition, we speculated that the light response elements are also related to the UV stress response. Ultraviolet radiation can affect plant growth and morphogenesis, especially in places with sufficient light, and high doses of UV-B, which can affect physiological and biochemical processes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we speculated that the light response elements are also related to the UV stress response. Ultraviolet radiation can affect plant growth and morphogenesis, especially in places with sufficient light, and high doses of UV-B, which can affect physiological and biochemical processes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The buckwheat is usually planted in habitats with low rainfall, low temperatures, and high altitudes [ 27 , 28 ]. In addition, sufficient light and ultraviolet radiation, for example, high UV-B doses, can affectthe physiological and biochemical processes of plants [ 29 31 ], contributing to unusual energy conversion efficiency and plant tissue function [ 32 ].To sum up, the growth, yield, and quality of buckwheat are severely threatened by abiotic stress factors or their combinations. To date, many transcription factors in Tartary buckwheat have been well-studied.…”
Section: Introductionmentioning
confidence: 99%
“…Trošt Sedej et al [ 40 ] reported that UV radiation increased stomatal conductance of Saxifraga hostii at high altitudes but not at low altitudes. S. hostii also showed trends for higher stomatal density and smaller stomatal length when exposed to the near-ambient UV, which corresponded to the higher stomatal conductance.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced UV-B radiation has an outcome in lowered chlorophyll contents in Zea mays and Citrus aurantifolia [ 47 , 48 ]. On the contrary, the chlorophyll contents increased in Saxifraga hostii under reduced UV-B radiation at montane and subalpine altitudes in September, which can indicate later senescence under reduced UV-B radiation [ 40 ]. High UV radiation can induce genes associated with senescence and consequently affect chlorophyll contents [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation